Tutor system in educational practice in Great Britain - E. A. Chelnokova; Z. I. Tyumaseva (Вестник Мининского университета, 2019)
Introduction: an Important task of national pedagogy is related to the understanding and analysis of the experience of educational systems of other countries that have a centuries-old pedagogical. The aim is to evaluate and use the most successful and effective developments of domestic pedagogy.The experience of the UK is leading in relation to the development of individualization of education. This experience is elite, as the traditional tutor training system has been developed and implemented for decades, it has proved its effectiveness in the course of interaction with many national pedagogical systems.Materials and methods: theoretical methods are fundamental for this study: the method of analogy of the concepts of mentoring, tutoring, support, maintenance; method of comparison, consisting in the consideration of the practice of tutoring from the Middle Ages to the present day and the experience of tutoring at different educational levels in the UK method of analyzing the experience of tutoring activities in educational practice in the UK and the experience of using the tutoring system in our days.Results: One of the most important elements of the educational system of great Britain is a method of tutor student interaction and student in teaching and education, the occurrence of which relates to the period of the middle Ages. Technology tutor support involves thoughtful and well-organized psychological and educational support, namely assistance to students in identifying and solving abilities to reconcile their desires with real possibilities in identifying opportunities for growth and advancement in personal development, in orientation in a rapidly changing world. During the entire period of study, the student needs guidance and support, including effective response to emerging issues, ensuring the implementation of needs as they arise.In the analysis of the tutor system of education as a means of improving the quality of education, we can not agree with the conclusion of many scientists, based on statistics from leading universities in England, that the improvement of academic achievements of students of both higher education institutions and schools is directly related to the tutor system of education.Discussion and conclusions: foreign experience, in our case English education, containing a constructive practice of improving the quality of the educational process, becomes relevant for modern Russian education. Studying and analyzing the experience of the organization of tutor support in England, we can determine the incentive for a wider awareness of pedagogical reality, more clearly see the problems and solutions and identify areas for further development of Russian education in this area.